On the Motion of Vortex Sheets with Surface Tension in the 3D Euler Equations with Vorticity - Cheng, C; Coutand, D; Shkoller, S (2007)
We prove well-posedness of vortex sheets with surface tension in the 3D incompressible Euler equations with vorticity.